src/HOL/Semiring_Normalization.thy
changeset 36845 d778c64fc35d
parent 36756 c1ae8a0b4265
child 36871 3763c349c8c1
equal deleted inserted replaced
36844:5f9385ecc1a7 36845:d778c64fc35d
    50   then show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z" by auto
    50   then show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z" by auto
    51 qed
    51 qed
    52 
    52 
    53 setup Semiring_Normalizer.setup
    53 setup Semiring_Normalizer.setup
    54 
    54 
    55 locale normalizing_semiring =
    55 lemma (in comm_semiring_1) semiring_ops:
    56   fixes add mul pwr r0 r1
    56   shows "TERM (x + y)" and "TERM (x * y)" and "TERM (x ^ n)"
    57   assumes add_a:"(add x (add y z) = add (add x y) z)"
    57     and "TERM 0" and "TERM 1" .
    58     and add_c: "add x y = add y x" and add_0:"add r0 x = x"
    58 
    59     and mul_a:"mul x (mul y z) = mul (mul x y) z" and mul_c:"mul x y = mul y x"
    59 lemma (in comm_semiring_1) semiring_rules:
    60     and mul_1:"mul r1 x = x" and  mul_0:"mul r0 x = r0"
    60   "(a * m) + (b * m) = (a + b) * m"
    61     and mul_d:"mul x (add y z) = add (mul x y) (mul x z)"
    61   "(a * m) + m = (a + 1) * m"
    62     and pwr_0:"pwr x 0 = r1" and pwr_Suc:"pwr x (Suc n) = mul x (pwr x n)"
    62   "m + (a * m) = (a + 1) * m"
    63 begin
    63   "m + m = (1 + 1) * m"
    64 
    64   "0 + a = a"
    65 lemma mul_pwr:"mul (pwr x p) (pwr x q) = pwr x (p + q)"
    65   "a + 0 = a"
    66 proof (induct p)
    66   "a * b = b * a"
    67   case 0
    67   "(a + b) * c = (a * c) + (b * c)"
    68   then show ?case by (auto simp add: pwr_0 mul_1)
    68   "0 * a = 0"
    69 next
    69   "a * 0 = 0"
    70   case Suc
    70   "1 * a = a"
    71   from this [symmetric] show ?case
    71   "a * 1 = a"
    72     by (auto simp add: pwr_Suc mul_1 mul_a)
    72   "(lx * ly) * (rx * ry) = (lx * rx) * (ly * ry)"
    73 qed
    73   "(lx * ly) * (rx * ry) = lx * (ly * (rx * ry))"
    74 
    74   "(lx * ly) * (rx * ry) = rx * ((lx * ly) * ry)"
    75 lemma pwr_mul: "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
    75   "(lx * ly) * rx = (lx * rx) * ly"
    76 proof (induct q arbitrary: x y, auto simp add:pwr_0 pwr_Suc mul_1)
    76   "(lx * ly) * rx = lx * (ly * rx)"
    77   fix q x y
    77   "lx * (rx * ry) = (lx * rx) * ry"
    78   assume "\<And>x y. pwr (mul x y) q = mul (pwr x q) (pwr y q)"
    78   "lx * (rx * ry) = rx * (lx * ry)"
    79   have "mul (mul x y) (mul (pwr x q) (pwr y q)) = mul x (mul y (mul (pwr x q) (pwr y q)))"
    79   "(a + b) + (c + d) = (a + c) + (b + d)"
    80     by (simp add: mul_a)
    80   "(a + b) + c = a + (b + c)"
    81   also have "\<dots> = (mul (mul y (mul (pwr y q) (pwr x q))) x)" by (simp add: mul_c)
    81   "a + (c + d) = c + (a + d)"
    82   also have "\<dots> = (mul (mul y (pwr y q)) (mul (pwr x q) x))" by (simp add: mul_a)
    82   "(a + b) + c = (a + c) + b"
    83   finally show "mul (mul x y) (mul (pwr x q) (pwr y q)) =
    83   "a + c = c + a"
    84     mul (mul x (pwr x q)) (mul y (pwr y q))" by (simp add: mul_c)
    84   "a + (c + d) = (a + c) + d"
    85 qed
    85   "(x ^ p) * (x ^ q) = x ^ (p + q)"
    86 
    86   "x * (x ^ q) = x ^ (Suc q)"
    87 lemma pwr_pwr: "pwr (pwr x p) q = pwr x (p * q)"
    87   "(x ^ q) * x = x ^ (Suc q)"
    88 proof (induct p arbitrary: q)
    88   "x * x = x ^ 2"
    89   case 0
    89   "(x * y) ^ q = (x ^ q) * (y ^ q)"
    90   show ?case using pwr_Suc mul_1 pwr_0 by (induct q) auto
    90   "(x ^ p) ^ q = x ^ (p * q)"
    91 next
    91   "x ^ 0 = 1"
    92   case Suc
    92   "x ^ 1 = x"
    93   thus ?case by (auto simp add: mul_pwr [symmetric] pwr_mul pwr_Suc)
    93   "x * (y + z) = (x * y) + (x * z)"
    94 qed
    94   "x ^ (Suc q) = x * (x ^ q)"
    95 
    95   "x ^ (2*n) = (x ^ n) * (x ^ n)"
    96 lemma semiring_ops:
    96   "x ^ (Suc (2*n)) = x * ((x ^ n) * (x ^ n))"
    97   shows "TERM (add x y)" and "TERM (mul x y)" and "TERM (pwr x n)"
    97   by (simp_all add: algebra_simps power_add power2_eq_square power_mult_distrib power_mult)
    98     and "TERM r0" and "TERM r1" .
       
    99 
       
   100 lemma semiring_rules:
       
   101   "add (mul a m) (mul b m) = mul (add a b) m"
       
   102   "add (mul a m) m = mul (add a r1) m"
       
   103   "add m (mul a m) = mul (add a r1) m"
       
   104   "add m m = mul (add r1 r1) m"
       
   105   "add r0 a = a"
       
   106   "add a r0 = a"
       
   107   "mul a b = mul b a"
       
   108   "mul (add a b) c = add (mul a c) (mul b c)"
       
   109   "mul r0 a = r0"
       
   110   "mul a r0 = r0"
       
   111   "mul r1 a = a"
       
   112   "mul a r1 = a"
       
   113   "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
       
   114   "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
       
   115   "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
       
   116   "mul (mul lx ly) rx = mul (mul lx rx) ly"
       
   117   "mul (mul lx ly) rx = mul lx (mul ly rx)"
       
   118   "mul lx (mul rx ry) = mul (mul lx rx) ry"
       
   119   "mul lx (mul rx ry) = mul rx (mul lx ry)"
       
   120   "add (add a b) (add c d) = add (add a c) (add b d)"
       
   121   "add (add a b) c = add a (add b c)"
       
   122   "add a (add c d) = add c (add a d)"
       
   123   "add (add a b) c = add (add a c) b"
       
   124   "add a c = add c a"
       
   125   "add a (add c d) = add (add a c) d"
       
   126   "mul (pwr x p) (pwr x q) = pwr x (p + q)"
       
   127   "mul x (pwr x q) = pwr x (Suc q)"
       
   128   "mul (pwr x q) x = pwr x (Suc q)"
       
   129   "mul x x = pwr x 2"
       
   130   "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
       
   131   "pwr (pwr x p) q = pwr x (p * q)"
       
   132   "pwr x 0 = r1"
       
   133   "pwr x 1 = x"
       
   134   "mul x (add y z) = add (mul x y) (mul x z)"
       
   135   "pwr x (Suc q) = mul x (pwr x q)"
       
   136   "pwr x (2*n) = mul (pwr x n) (pwr x n)"
       
   137   "pwr x (Suc (2*n)) = mul x (mul (pwr x n) (pwr x n))"
       
   138 proof -
       
   139   show "add (mul a m) (mul b m) = mul (add a b) m" using mul_d mul_c by simp
       
   140 next show"add (mul a m) m = mul (add a r1) m" using mul_d mul_c mul_1 by simp
       
   141 next show "add m (mul a m) = mul (add a r1) m" using mul_c mul_d mul_1 add_c by simp
       
   142 next show "add m m = mul (add r1 r1) m" using mul_c mul_d mul_1 by simp
       
   143 next show "add r0 a = a" using add_0 by simp
       
   144 next show "add a r0 = a" using add_0 add_c by simp
       
   145 next show "mul a b = mul b a" using mul_c by simp
       
   146 next show "mul (add a b) c = add (mul a c) (mul b c)" using mul_c mul_d by simp
       
   147 next show "mul r0 a = r0" using mul_0 by simp
       
   148 next show "mul a r0 = r0" using mul_0 mul_c by simp
       
   149 next show "mul r1 a = a" using mul_1 by simp
       
   150 next show "mul a r1 = a" using mul_1 mul_c by simp
       
   151 next show "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
       
   152     using mul_c mul_a by simp
       
   153 next show "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
       
   154     using mul_a by simp
       
   155 next
       
   156   have "mul (mul lx ly) (mul rx ry) = mul (mul rx ry) (mul lx ly)" by (rule mul_c)
       
   157   also have "\<dots> = mul rx (mul ry (mul lx ly))" using mul_a by simp
       
   158   finally
       
   159   show "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
       
   160     using mul_c by simp
       
   161 next show "mul (mul lx ly) rx = mul (mul lx rx) ly" using mul_c mul_a by simp
       
   162 next
       
   163   show "mul (mul lx ly) rx = mul lx (mul ly rx)" by (simp add: mul_a)
       
   164 next show "mul lx (mul rx ry) = mul (mul lx rx) ry" by (simp add: mul_a )
       
   165 next show "mul lx (mul rx ry) = mul rx (mul lx ry)" by (simp add: mul_a,simp add: mul_c)
       
   166 next show "add (add a b) (add c d) = add (add a c) (add b d)"
       
   167     using add_c add_a by simp
       
   168 next show "add (add a b) c = add a (add b c)" using add_a by simp
       
   169 next show "add a (add c d) = add c (add a d)"
       
   170     apply (simp add: add_a) by (simp only: add_c)
       
   171 next show "add (add a b) c = add (add a c) b" using add_a add_c by simp
       
   172 next show "add a c = add c a" by (rule add_c)
       
   173 next show "add a (add c d) = add (add a c) d" using add_a by simp
       
   174 next show "mul (pwr x p) (pwr x q) = pwr x (p + q)" by (rule mul_pwr)
       
   175 next show "mul x (pwr x q) = pwr x (Suc q)" using pwr_Suc by simp
       
   176 next show "mul (pwr x q) x = pwr x (Suc q)" using pwr_Suc mul_c by simp
       
   177 next show "mul x x = pwr x 2" by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
       
   178 next show "pwr (mul x y) q = mul (pwr x q) (pwr y q)" by (rule pwr_mul)
       
   179 next show "pwr (pwr x p) q = pwr x (p * q)" by (rule pwr_pwr)
       
   180 next show "pwr x 0 = r1" using pwr_0 .
       
   181 next show "pwr x 1 = x" unfolding One_nat_def by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
       
   182 next show "mul x (add y z) = add (mul x y) (mul x z)" using mul_d by simp
       
   183 next show "pwr x (Suc q) = mul x (pwr x q)" using pwr_Suc by simp
       
   184 next show "pwr x (2 * n) = mul (pwr x n) (pwr x n)" by (simp add: nat_number' mul_pwr)
       
   185 next show "pwr x (Suc (2 * n)) = mul x (mul (pwr x n) (pwr x n))"
       
   186     by (simp add: nat_number' pwr_Suc mul_pwr)
       
   187 qed
       
   188 
       
   189 end
       
   190 
       
   191 sublocale comm_semiring_1
       
   192   < normalizing!: normalizing_semiring plus times power zero one
       
   193 proof
       
   194 qed (simp_all add: algebra_simps)
       
   195 
    98 
   196 lemmas (in comm_semiring_1) normalizing_comm_semiring_1_axioms =
    99 lemmas (in comm_semiring_1) normalizing_comm_semiring_1_axioms =
   197   comm_semiring_1_axioms [normalizer
   100   comm_semiring_1_axioms [normalizer
   198     semiring ops: normalizing.semiring_ops
   101     semiring ops: semiring_ops
   199     semiring rules: normalizing.semiring_rules]
   102     semiring rules: semiring_rules]
   200 
   103 
   201 declaration (in comm_semiring_1)
   104 declaration (in comm_semiring_1)
   202   {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_axioms} *}
   105   {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_axioms} *}
   203 
   106 
   204 locale normalizing_ring = normalizing_semiring +
   107 lemma (in comm_ring_1) ring_ops: shows "TERM (x- y)" and "TERM (- x)" .
   205   fixes sub :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
   108 
   206     and neg :: "'a \<Rightarrow> 'a"
   109 lemma (in comm_ring_1) ring_rules:
   207   assumes neg_mul: "neg x = mul (neg r1) x"
   110   "- x = (- 1) * x"
   208     and sub_add: "sub x y = add x (neg y)"
   111   "x - y = x + (- y)"
   209 begin
   112   by (simp_all add: diff_minus)
   210 
       
   211 lemma ring_ops: shows "TERM (sub x y)" and "TERM (neg x)" .
       
   212 
       
   213 lemmas ring_rules = neg_mul sub_add
       
   214 
       
   215 end
       
   216 
       
   217 sublocale comm_ring_1
       
   218   < normalizing!: normalizing_ring plus times power zero one minus uminus
       
   219 proof
       
   220 qed (simp_all add: diff_minus)
       
   221 
   113 
   222 lemmas (in comm_ring_1) normalizing_comm_ring_1_axioms =
   114 lemmas (in comm_ring_1) normalizing_comm_ring_1_axioms =
   223   comm_ring_1_axioms [normalizer
   115   comm_ring_1_axioms [normalizer
   224     semiring ops: normalizing.semiring_ops
   116     semiring ops: semiring_ops
   225     semiring rules: normalizing.semiring_rules
   117     semiring rules: semiring_rules
   226     ring ops: normalizing.ring_ops
   118     ring ops: ring_ops
   227     ring rules: normalizing.ring_rules]
   119     ring rules: ring_rules]
   228 
   120 
   229 declaration (in comm_ring_1)
   121 declaration (in comm_ring_1)
   230   {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_ring_1_axioms} *}
   122   {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_ring_1_axioms} *}
   231 
   123 
   232 locale normalizing_semiring_cancel = normalizing_semiring +
   124 lemma (in comm_semiring_1_cancel_norm) noteq_reduce:
   233   assumes add_cancel: "add (x::'a) y = add x z \<longleftrightarrow> y = z"
   125   "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> (a * c) + (b * d) \<noteq> (a * d) + (b * c)"
   234   and add_mul_solve: "add (mul w y) (mul x z) =
       
   235     add (mul w z) (mul x y) \<longleftrightarrow> w = x \<or> y = z"
       
   236 begin
       
   237 
       
   238 lemma noteq_reduce: "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
       
   239 proof-
   126 proof-
   240   have "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> \<not> (a = b \<or> c = d)" by simp
   127   have "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> \<not> (a = b \<or> c = d)" by simp
   241   also have "\<dots> \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
   128   also have "\<dots> \<longleftrightarrow> (a * c) + (b * d) \<noteq> (a * d) + (b * c)"
   242     using add_mul_solve by blast
   129     using add_mult_solve by blast
   243   finally show "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
   130   finally show "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> (a * c) + (b * d) \<noteq> (a * d) + (b * c)"
   244     by simp
   131     by simp
   245 qed
   132 qed
   246 
   133 
   247 lemma add_scale_eq_noteq: "\<lbrakk>r \<noteq> r0 ; (a = b) \<and> ~(c = d)\<rbrakk>
   134 lemma (in comm_semiring_1_cancel_norm) add_scale_eq_noteq:
   248   \<Longrightarrow> add a (mul r c) \<noteq> add b (mul r d)"
   135   "\<lbrakk>r \<noteq> 0 ; a = b \<and> c \<noteq> d\<rbrakk> \<Longrightarrow> a + (r * c) \<noteq> b + (r * d)"
   249 proof(clarify)
   136 proof(clarify)
   250   assume nz: "r\<noteq> r0" and cnd: "c\<noteq>d"
   137   assume nz: "r\<noteq> 0" and cnd: "c\<noteq>d"
   251     and eq: "add b (mul r c) = add b (mul r d)"
   138     and eq: "b + (r * c) = b + (r * d)"
   252   hence "mul r c = mul r d" using cnd add_cancel by simp
   139   have "(0 * d) + (r * c) = (0 * c) + (r * d)"
   253   hence "add (mul r0 d) (mul r c) = add (mul r0 c) (mul r d)"
   140     using add_imp_eq eq mult_zero_left by simp
   254     using mul_0 add_cancel by simp
   141   thus "False" using add_mult_solve[of 0 d] nz cnd by simp
   255   thus "False" using add_mul_solve nz cnd by simp
   142 qed
   256 qed
   143 
   257 
   144 lemma (in comm_semiring_1_cancel_norm) add_0_iff:
   258 lemma add_r0_iff: " x = add x a \<longleftrightarrow> a = r0"
   145   "x = x + a \<longleftrightarrow> a = 0"
   259 proof-
   146 proof-
   260   have "a = r0 \<longleftrightarrow> add x a = add x r0" by (simp add: add_cancel)
   147   have "a = 0 \<longleftrightarrow> x + a = x + 0" using add_imp_eq[of x a 0] by auto
   261   thus "x = add x a \<longleftrightarrow> a = r0" by (auto simp add: add_c add_0)
   148   thus "x = x + a \<longleftrightarrow> a = 0" by (auto simp add: add_commute)
   262 qed
   149 qed
   263 
       
   264 end
       
   265 
       
   266 sublocale comm_semiring_1_cancel_norm
       
   267   < normalizing!: normalizing_semiring_cancel plus times power zero one
       
   268 proof
       
   269 qed (simp_all add: add_mult_solve)
       
   270 
   150 
   271 declare (in comm_semiring_1_cancel_norm)
   151 declare (in comm_semiring_1_cancel_norm)
   272   normalizing_comm_semiring_1_axioms [normalizer del]
   152   normalizing_comm_semiring_1_axioms [normalizer del]
   273 
   153 
   274 lemmas (in comm_semiring_1_cancel_norm)
   154 lemmas (in comm_semiring_1_cancel_norm)
   275   normalizing_comm_semiring_1_cancel_norm_axioms =
   155   normalizing_comm_semiring_1_cancel_norm_axioms =
   276   comm_semiring_1_cancel_norm_axioms [normalizer
   156   comm_semiring_1_cancel_norm_axioms [normalizer
   277     semiring ops: normalizing.semiring_ops
   157     semiring ops: semiring_ops
   278     semiring rules: normalizing.semiring_rules
   158     semiring rules: semiring_rules
   279     idom rules: normalizing.noteq_reduce normalizing.add_scale_eq_noteq]
   159     idom rules: noteq_reduce add_scale_eq_noteq]
   280 
   160 
   281 declaration (in comm_semiring_1_cancel_norm)
   161 declaration (in comm_semiring_1_cancel_norm)
   282   {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_cancel_norm_axioms} *}
   162   {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_cancel_norm_axioms} *}
   283 
   163 
   284 locale normalizing_ring_cancel = normalizing_semiring_cancel + normalizing_ring + 
       
   285   assumes subr0_iff: "sub x y = r0 \<longleftrightarrow> x = y"
       
   286 
       
   287 sublocale idom
       
   288   < normalizing!: normalizing_ring_cancel plus times power zero one minus uminus
       
   289 proof
       
   290 qed simp
       
   291 
       
   292 declare (in idom) normalizing_comm_ring_1_axioms [normalizer del]
   164 declare (in idom) normalizing_comm_ring_1_axioms [normalizer del]
   293 
   165 
   294 lemmas (in idom) normalizing_idom_axioms = idom_axioms [normalizer
   166 lemmas (in idom) normalizing_idom_axioms = idom_axioms [normalizer
   295   semiring ops: normalizing.semiring_ops
   167   semiring ops: semiring_ops
   296   semiring rules: normalizing.semiring_rules
   168   semiring rules: semiring_rules
   297   ring ops: normalizing.ring_ops
   169   ring ops: ring_ops
   298   ring rules: normalizing.ring_rules
   170   ring rules: ring_rules
   299   idom rules: normalizing.noteq_reduce normalizing.add_scale_eq_noteq
   171   idom rules: noteq_reduce add_scale_eq_noteq
   300   ideal rules: normalizing.subr0_iff normalizing.add_r0_iff]
   172   ideal rules: right_minus_eq add_0_iff]
   301 
   173 
   302 declaration (in idom)
   174 declaration (in idom)
   303   {* Semiring_Normalizer.semiring_funs @{thm normalizing_idom_axioms} *}
   175   {* Semiring_Normalizer.semiring_funs @{thm normalizing_idom_axioms} *}
   304 
   176 
   305 locale normalizing_field = normalizing_ring_cancel +
   177 lemma (in field) field_ops:
   306   fixes divide :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
   178   shows "TERM (x / y)" and "TERM (inverse x)" .
   307     and inverse:: "'a \<Rightarrow> 'a"
   179 
   308   assumes divide_inverse: "divide x y = mul x (inverse y)"
   180 lemmas (in field) field_rules = divide_inverse inverse_eq_divide
   309      and inverse_divide: "inverse x = divide r1 x"
       
   310 begin
       
   311 
       
   312 lemma field_ops: shows "TERM (divide x y)" and "TERM (inverse x)" .
       
   313 
       
   314 lemmas field_rules = divide_inverse inverse_divide
       
   315 
       
   316 end
       
   317 
       
   318 sublocale field 
       
   319   < normalizing!: normalizing_field plus times power zero one minus uminus divide inverse
       
   320 proof
       
   321 qed (simp_all add: divide_inverse)
       
   322 
   181 
   323 lemmas (in field) normalizing_field_axioms =
   182 lemmas (in field) normalizing_field_axioms =
   324   field_axioms [normalizer
   183   field_axioms [normalizer
   325     semiring ops: normalizing.semiring_ops
   184     semiring ops: semiring_ops
   326     semiring rules: normalizing.semiring_rules
   185     semiring rules: semiring_rules
   327     ring ops: normalizing.ring_ops
   186     ring ops: ring_ops
   328     ring rules: normalizing.ring_rules
   187     ring rules: ring_rules
   329     field ops: normalizing.field_ops
   188     field ops: field_ops
   330     field rules: normalizing.field_rules
   189     field rules: field_rules
   331     idom rules: normalizing.noteq_reduce normalizing.add_scale_eq_noteq
   190     idom rules: noteq_reduce add_scale_eq_noteq
   332     ideal rules: normalizing.subr0_iff normalizing.add_r0_iff]
   191     ideal rules: right_minus_eq add_0_iff]
   333 
   192 
   334 declaration (in field)
   193 declaration (in field)
   335   {* Semiring_Normalizer.field_funs @{thm normalizing_field_axioms} *}
   194   {* Semiring_Normalizer.field_funs @{thm normalizing_field_axioms} *}
   336 
   195 
       
   196 hide_fact (open) normalizing_comm_semiring_1_axioms
       
   197   normalizing_comm_semiring_1_cancel_norm_axioms semiring_ops semiring_rules
       
   198 
       
   199 hide_fact (open) normalizing_comm_ring_1_axioms
       
   200   normalizing_idom_axioms ring_ops ring_rules
       
   201 
       
   202 hide_fact (open)  normalizing_field_axioms field_ops field_rules
       
   203 
       
   204 hide_fact (open) add_scale_eq_noteq noteq_reduce
       
   205 
   337 end
   206 end